A Prospective Study in Detection of Lower-Limb Lymphedema and Evaluation of Quality of Life After Vulvar Cancer Surgery. Issue 6 (1st July 2012) - Novackova, Marta; Halaska, Michael J.; Robova, Helena; Mala, Ivana; Pluta, Marek; Chmel, Roman; Rob, Lukas
Abstract : Background: Lower-limb lymphedema is one of the most disabling adverse effects of vulvar cancer surgery. Multifrequency Bioelectrical Impedance Analysis (MFBIA) is a modern noninvasive method to detect lymphedema. The first aim of this study was to prospectively determine the prevalence of secondary lower-limb lymphedema after surgical treatment for vulvar cancer using objective methods, circumference measurements and MFBIA technique. The second aim was to compare quality of life (QoL) before and 6 months after vulvar surgery. Methods: Twenty-nine patients underwent vulvar cancer surgery in our study: 17 underwent inguinofemoral lymphadenectomy (RAD), and 12 underwent sentinel lymph node biopsy (CONS). Patients were examined before and 6 months after vulvar surgery by measuring the circumference of the lower limbs and with MFBIA. A control group of 27 healthy women was also measured. To evaluate QoL, the European Organisation for Research and Treatment of Cancer (EORTC) QoL questionnaires (QLQ-C30 and QLQ-CX24) were administered to patients before and 6 months after surgery. Results: Using circumference measurement, 9 lymphedemas (31%) were diagnosed: 3 (25%) in the CONS and 6 (37.5%) in the RAD group ( P = 0.69). After vulvar surgery, patients in the RAD group reported more fatigue and worsening of physical and role functioning. When comparing both groups, the RAD group had significantly worse parameters in social functioning, fatigue, and dyspnea. Conclusions: Lower radicality in inguinofemoral lymphadenectomy shows a trend toward lower morbidity and significantly improves QoL. Multifrequency Bioelectrical Impedance Analysis was tested in these patients as a noninvasive, objective method for lymphedema detection. Detection of lymphedema based on subjective evaluations proved to have an unsatisfactory sensitivity. Less radical surgery showed objectively better results in QoL.